Digital mining oversight for risk management optimization - Yuwan Martus Tegar Charisma; Zulkifli Djunaidi; Mufti Wirawan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Coal mining operations involve high-risk activities that require effective oversight and comprehensive risk management to prevent occupational accidents, operational disruptions, and financial losses. Despite increasing digital transformation initiatives within the mining sector, studies examining the effectiveness of digital oversight systems in supporting risk management remain limited, particularly among Indonesian coal mining contractors. Purpose: This study aimed to evaluate the implementation of digital systems in mining oversight at PT X, a coal mining contractor in Indonesia. Method: A qualitative case-study approach was employed using in-depth interviews with key informants, field observations, and document reviews. Data were analyzed through thematic analysis and triangulation to evaluate the implementation of digital technologies integrated into operational supervision and risk-management processes. Results: The findings revealed that PT X implemented several digital oversight technologies, including QHSE Automation, digital mining-sign monitoring, Slope Stability Radar (SSR), dashboard-based analytics, and Mining Eyes (CCTV) systems. These technologies improved real-time monitoring, hazard reporting, corrective-action tracking, and operational visibility. The implementation of digital systems contributed to a reduction of more than 20% in the Incident Frequency Rate and a 77% reduction in incident cost. Furthermore, digitalization improved hazard identification, accelerated risk-control processes, strengthened supervisory effectiveness, and supported data-driven decision making. Conclusion: Digitalization plays an important role in strengthening risk management and improving oversight effectiveness within mining operations. The integration of digital technologies supports proactive hazard management, improves safety performance, enhances operational efficiency, and contributes to safer and more sustainable mining practices.